Rancang Bangun Aplikasi Pengiriman Barang Berbasis Website Pada PT Dunia Parcel Express - Irvan Trinanda; Popong Setiawati (CV. Multi Kreasi Media, 2022)
Dunia Parcel Express is a local Indonesian company founded in 2001. Originally started as a courier company, over the years the company with its enriched team talent and initiative, has diversifiedand added to its laurels a variety of other value-added logistics services. The inclusion of such services has enabled us to become a one-stopsolution and service provider. In the application for shipping goods. PT Dunia Parcel Express still uses a simple method (not yet fully computerized) and has experienced delays in processing data. So that in making strategic decisions it will be too late. The purpose of his Final Project is to create a website application that can make it easier for customers to send their goods and also later customers can track goods to see where the goods have been sent by entering the customer’s receipt number. This application can later appear on a pc or laptop and is made using the php programming language with a MySql database in the form of implementing Web- based applications. Later, after the shipping website is complete, it will then be hosted. Hopefully by making this application it is hoped that it can integrate data from each work function, as well a provide all kinds of information that can be accessed and processed in one system quickly and improve good service